Robotics: Hephaestus does it again - Jean-Paul Laumond (Collège de France, 2012)
It was when I was preparing this lecture that I discovered that roboticists had a god: Hephaestus. In Greek mythology, Hephaestus was a talented craftsman. Enamoured with Athena, he attempted to woo her, in vain. The goddess of knowledge withstood the advances of the god of doing. Robotics stems from this tension. Although the myth contradicts a current tendency to confuse science and technology, it nevertheless reflects my experience with innovation. C'est en préparant cette leçon que j'ai ...